Scale Reduction in Oil Pipes Using Pineapple Peel Acetic Acid and HCL: A Laboratory Study - Novrianti; Arjun Anggara P; Neneng Purnamawati; M. Ridha Fikri (Lembaran publikasi minyak dan gas bumi, 2026)
The reduction in oil production rates due to the formation of calcium carbonate (CaCO₃) scale deposits on production pipes is a common problem in upstream oil and gas operations. This study aims to evaluate the effectiveness of acetic acid produced from pineapple peel fermentation, alone and in combination with hydrochloric acid (HCl), as an organic-based scale-removal agent, with EDTA-2Na used as a comparison via chelation. The research methods included acetic acid extraction via two-stage fermentation, characterization of functional groups by infrared spectroscopy (FTIR), and analysis of mineral scale composition by X-ray fluorescence (XRF). Scale testing was carried out using the weight-loss method with immersion times of 30, 60, and 90 minutes. FTIR results showed the presence of characteristic organic acid functional groups, while XRF results confirmed that the scale was dominated by calcium as the main component of CaCO₃. The test results showed that the mixture of acetic acid and HCl provided the highest effectiveness with a mass loss of 0.43 grams at 90 minutes, followed by pure acetic acid at 0.36 grams, while EDTA-2Na produced a reduction of 0.08 grams. These results indicate that biomass-based acetic acid has the potential to be a more environmentally friendly alternative for scale removal in oil and gas production piping systems.